Indoor urban agriculture: from innovative design experimentation to standardisation - Maicol Negrello (Techne)
The need to reconfigure current supply models to address future climate and demographic scenarios has driven researchers and investors to experiment with innovative production systems that have reconnected agricultural production to the point of consumption, namely cities. The technological acceleration of the past decade has led to the emergence of new urban architectures and metabolisms, often created within regulatory gaps and constraints arising from the obsolescence of zoning plans or building regulations. This paper outlines the state of the art of technological innovation and how, along with design, it has reshaped norms.